Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This is more related to engineering but I am having difficulty to draw the connection.

I have the following predicate a$\to$(b$\to$c) and I would like to find P$_{(a=T)}$ $\oplus$ P$_{(a=F)}$

I am doing the following:


P$_{(a=F)}$=F$\to$(b$\to$c)=(b$\to$c) $\lor$ $\lnot$(b$\to$c)

Finally I get T, which turned out to be wrong as the correct answer is b $\land$$\lnot$c

I tried to find reference that would help refresh my logic math memory but couldn't find any. The scope I need include similar operations done to $\leftarrow$$\rightarrow$ (couldn't find it in mathjax) and $\oplus$


share|cite|improve this question
up vote 1 down vote accepted

We have $P_{\{a = F\}} \equiv F \to (b \to c) \equiv T$ (ex falso quodlibet, a statement $p\to q$ is always true, is $p$ is false). So $P_{\{a = T\}}\oplus P_{\{a = F\}} \equiv P_{a = T} \oplus T = \neg P_{\{a = T\}}$. Now $P_{\{a = T\}}= b\to c \equiv \neg b \lor c$, and hence $$ P_{\{a = T\}}\oplus P_{\{a = F\}} \equiv \neg P_{\{a = T\}} \equiv \neg(\neg b \lor c) \equiv b \land \neg c. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.